Mortality and Complication Rates in Adult Trauma Patients Receiving Tranexamic Acid: A Single‐center Experience in the Post–CRASH‐2 Era. (19th March 2020) - Erramouspe, Pablo Joaquin; García‐Pintos, María Florencia; Benipal, Simranjeet; Manoukian, Martin A. C.; Santamarina, John‐Lloyd; Shawagga, Hiwote G.; Vo, Linda L.; Galante, Joseph M.; Nishijima, Daniel
Abstract: Objectives: The CRASH‐2 trial demonstrated that tranexamic acid (TXA) in adults with significant traumatic hemorrhage safely reduces mortality. Given that the CRASH‐2 trial did not include U.S. sites, our objective was to evaluate patient characteristics, TXA dosing strategies, and the incidence of mortality and adverse events in adult trauma patients receiving TXA at a U.S. Level I trauma center in the post–CRASH‐2 era. Methods: We conducted a retrospective study that included patients aged 18 years or older who received TXA after an acute injury from July 2014 to June 2017 . We excluded patients who received TXA orally, patients who received TXA for elective surgical procedures or nontrauma indications, patients who received it 8 hours or longer after the time of injury, and patients with cardiac arrest at time of emergency department arrival. Trained abstractors collected data from the trauma registry and hospital electronic medical records. Our primary outcome measures were in‐hospital death and acute thromboembolic events within 28 days from injury. Results: We included 273 patients with a mean (±SD) age of 43.8 (±18.7) years. The mean (±SD) time of administration of TXA from time of injury was 1.55 (±1.2) hours with 229 patients (83.9%) receiving TXA within 3 hours. The overall mortality within 28 days from injury was 12.8% (95% confidence interval [CI] = 8.9% to 16.7%), which was similar compared to that in the CRASH‐2 trial (14.5%, 95% CI = 13.9% to 15.2%). The incidence of acute thromboembolic events was 6.6% (95% CI = 3.7% to 9.5%), which was higher than that in the CRASH‐2 trial (2.0%, 95% CI = 1.73% to 2.27%). Patients in our cohort also received surgery (64.8% vs. 47.9%) and blood transfusions (74.0% vs. 50.4%) more frequently than those in the CRASH‐2 cohort. Conclusions: Adult trauma patients receiving TXA had similar incidences of death but higher incidences of thromboembolic events compared to the CRASH‐2 trial. Variation in patient characteristics, injury severity, TXA dosing, and surgery and transfusion rates could explain these observed differences. Further research is necessary to provide additional insight into the incidence and risk factors of thromboembolic events in TXA use.